2019
DOI: 10.1101/782219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altering Polycomb Repressive Complex 2 activity partially suppressesddm1mutant phenotypes in Arabidopsis

Abstract: 14In plants and mammals, DNA methylation is a hallmark of transposable element (TE) 15 sequences that contributes to their epigenetic silencing. In contrast, histone H3 lysine 27 16 trimethylation (H3K27me3), which is deposited by the Polycomb Repressive Complex 2 17 (PRC2), is a hallmark of repressed genes. Nevertheless, there is a growing body of evidence for 18 a functional interplay between these pathways. In particular, many TE sequences acquire 19H3K27me3 when they lose DNA methylation and it has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Additionally, analysis of the Arabidopsis met1 mutant has shown that a large number of TEs that lose DNA methylation gain H3K27me3 ( Deleris et al, 2012 ). Similarly, TEs in Arabidopsis gain H3K27me3 in response to ddm1 -induced loss of DNA methylation ( Rougée et al, 2020 ). Collectively, our data together with these reports suggest that DNA methylation and H3K27me3 act antagonistically to mediate the transcriptional silencing of transposons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, analysis of the Arabidopsis met1 mutant has shown that a large number of TEs that lose DNA methylation gain H3K27me3 ( Deleris et al, 2012 ). Similarly, TEs in Arabidopsis gain H3K27me3 in response to ddm1 -induced loss of DNA methylation ( Rougée et al, 2020 ). Collectively, our data together with these reports suggest that DNA methylation and H3K27me3 act antagonistically to mediate the transcriptional silencing of transposons.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to heterochromatin are known to occur in the angiosperm female gametophyte, where the reduction in DNA and H3K9 methylation coincides with a redistribution of H3K27me3 to a large proportion of TEs (Weinhofer et al 2010). Accumulation of H3K27me3 at TEs also occurs in mutants affecting constitutive heterochromatin in fungi, animals and even plants (Reddington et al 2013;Jamieson et al 2016;Rougée et al 2019). We have already highlighted how transposons and repeats are marked by H3K27me3 in unicellular red algae and green algae (Fig.…”
Section: The Origin Of Prc2 Lies In the Silencing Of Transposonsmentioning
confidence: 89%
“…However, a recent deep repeat annotation revealed traces of uncharacterized TEs within FLC [37]. Interestingly, numerous TEs that lose DNA methylation in mutants deficient in MET1 or the chromatin remodeler DDM1, as well as in the endosperm of wild-type seeds, gain ectopic H3K27me3 [38][39][40][41], indicating that unmethylated TEs can be targeted by PCR2. Therefore, it is reasonable to speculate that the accumulation of old, highly degenerated and unmethylated TE sequences within FLC may have contributed to the evolution of this notable intron and its epigenetic regulation.…”
Section: An Unusually Long Intron Integrates the Epigenetic Regulatiomentioning
confidence: 99%